Role of tobacco in pandemic COVID-19 in India - Gupta, Ankit; Dutt, Bheem; Singh, Mahendra (International Journal Of Community Medicine And Public Health, 2022)
Since the end of 2019, the world has witnessed the spread of a COVID-19, that affects the respiratory system of the body in the form of the novel coronavirus. This pandemic has affected people across all socioeconomic demographics and cultures in high-, middle- and low- income countries. Tobacco is also a major risk factor for many diseases like cardiovascular disease, cancer, respiratory disease and diabetes which put people with these conditions at higher risk for developing severe illness when affected by COVID-19. Minimizing the use of tobacco and smoking might be an important factor for containing COVID-19 infection. On the other side, studies also suggest also that smoking is associated with a decreased risk of hospital admission with a diagnosis of COVID-19, or a decreased risk of occurrence of the disease in the community. These studies have noted 4 to 5 times lower proportions of smokers among patients hospitalized for COVID-19 compared with the underlying source population. A metanalysis of hospital case series confirmed this gap.